Validation and comparison of quality‐of‐life measures for topical 5‐fluorouracil treatment: results from a randomized controlled trial. (1st July 2017) - Pomerantz, H.; Chren, M.‐M.; Lew, R.; Weinstock, M. A.; ,; Hogan, D; Eilers, D.; Swetter, S.; Chen, S. C.; Jacob, S.; Warshaw, E. M.; Stricklin, G.; et al.
Summary: Background: Topical 5‐fluorouracil (5‐FU) is commonly used for high‐risk patients with keratinocyte carcinoma (KC). Skindex and Skin Cancer Index (SCI) are validated instruments to measure quality of life (QoL) of patients with KC and those who have had surgical treatment of KCs. Aim: To validate Skindex and SCI for topical 5‐fluorouracil (5‐FU) application and to compare the two QoL instruments. Methods: We randomized 932 veterans at high risk for developing a KC to either topical 5‐FU or vehicle control cream applied to the face and ears for up to 1 month. We collected their Skindex‐29 and SCI scores at baseline and follow‐up visits. Results: Compared with controls, 5‐FU reduced QoL, measured by the Skindex symptom, Skindex function and SCI social subscales ( P < 0.001, P < 0.01, P = 0.02, respectively). At 1 month, significant changes in QoL in the 5‐FU group were observed in the Skindex symptom (10.1, 95% CI 0.36–12.6), Skindex function (6.0, 95% CI 4.0–8.0) and SCI social (−3.5, 95% CI −6.2 to −0.8) subscales, while the other subscales of Skindex and SCI did not show significant changes. All three Skindex subscales at 1 month correlated with patient‐reported symptom score and photograph‐based toxicity score, whereas social subscale was the only one of the SCI subscales that correlated with patient‐reported symptom and photograph‐based toxicity scores. Conclusions: Our study validated Skindex symptom, Skindex function and SCI social subscales for QoL measurement during treatment with topical 5‐FU. The study could not provide evidence for construct validity of the other subscales. Skindex was more responsive than SCI in the context of 5‐FU treatment.